Effect of ABT-263 on Intestinal Fibrosis in Human Myofibroblasts, Human Intestinal Organoids, and the Mouse Salmonella typhimurium Model. Issue 2 (24th July 2021) - Johnson, Laura A; Rodansky, Eva S; Tran, Anhdao; Collins, Stephen G; Eaton, Kathryn A; Malamet, Benjamin; Steiner, Calen A; Huang, Sha; Spence, Jason R; Higgins, Peter D R
Abstract: Background: Intestinal fibrosis and subsequent intestinal obstruction are common complications of Crohn's disease (CD). Current therapeutics combat inflammation, but no pharmacological therapy exists for fibrostenotic disease. Pathological persistence of activated intestinal myofibroblasts is a key driver of fibrosis in CD. In other organ systems, BH-3 mimetic drugs that affect Bcl-2 apoptotic pathways induce apoptosis in activated myofibroblasts and reduce fibrogenic gene expression, thereby reducing fibrosis. Methods: We evaluated the proapoptotic and antifibrotic efficacy of several classes of BH-3 mimetics in 2 in vitro fibrogenesis models. The candidate molecule, ABT-263, was advanced to a 3-dimensional human intestinal organoid (HIO) model. Finally, the therapeutic efficacy of ABT-263 was evaluated in the mouse Salmonella typhimurium intestinal fibrosis model. Results: The BH-3 mimetics induced apoptosis, repressed fibrotic protein expression, and reduced fibrogenic gene expression in normal human intestinal myofibroblasts. The BH-3 mimetics that target Bcl-2 and Bcl-xl demonstrated the greatest efficacy in vitro. The ABT-199 and ABT-263 induced apoptosis and ameliorated fibrogenesis in the in vitro myofibroblast models. In the HIO model, ABT-263 inhibited fibrogenesis and induced apoptosis. In the mouse S. typhimurium model, dose-dependent reduction in macroscopic pathology, histological inflammation, inflammatory and fibrotic gene expression, and extracellular matrix protein expression indicated ABT-263 may reduce intestinal fibrosis. Conclusions: In vitro, the antifibrotic efficacy of BH-3 mimetics identifies the Bcl-2 pathway as a druggable target and BH-3 mimetics as putative therapeutics. Reduction of inflammation and fibrosis in the mouse intestinal fibrosis model by ABT-263 indicates BH-3 mimetics as potential, novel antifibrotic therapeutics for Crohn's disease. Lay Summary: Intestinal fibrosis is a common complication of Crohn's disease, yet no effective therapies exist to treat fibrostenotic disease. We report ABT-263 (navitoclax) reduces intestinal fibrosis in in vitro models and reduces inflammation and fibrosis in a mouse IBD model.